Pixel-based dispersal scheme for medical image survivability and confidentiality - Nelmiawati, 1989- 1989- author (Johor Bahru, Johor: Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2014